Low Plasma Carotenoids and Skeletal Muscle Strength Decline over Six Years - Lauretani, Fulvio (2008)
BACKGROUND: Higher intake of fruits and vegetables appears to protect against inflammation, poor physical performance, and disability, but their relationship with muscle strength is unclear. We examined the association between total plasma carotenoids, an indicator of fruit and vegetable intake, and changes in muscle strength over a 6-year follow-up in the participants aged 65 years and older in the InCHIANTI study, a population-based study in Tuscany, Italy. METHODS: Plasma carotenoids were measured at enrollment (1998–2000). Hip, knee and grip strength were measured at enrollment and 6 years later (2004–2006) in 628 of the 948 participants evaluated at baseline. Poor muscle strength was defined as the lowest sex-specific quartile of hip, knee and grip strength at enrollment. The main outcome was poor muscle strength at the six-year follow-up visit among those originally in the upper three quartiles of strength at enrollment. RESULTS: Overall, 24.9% (110/441), 25.0% (111/444) and 24.9% (118/474) participants developed poor hip, knee and grip strength, respectively. After adjusting for potential confounders, participants in the lowest vs. the highest quartile of total plasma carotenoids at enrollment were at higher risk of developing poor hip (O.R. 2.25, 95% C.I. 1.13–4.48, P = 0.02), knee (O.R. 2.12, 95% C.I. 1.08–4.09, P = 0.03) and grip (O.R. 1.85, 95% C.I. 0.95–3.61, P = 0.07) muscle strength at the six-year follow-up visit. CONCLUSION: These findings suggest that older community-dwelling adults with lower plasma carotenoids levels, a marker of poor fruit and vegetable intake, are at a higher risk of decline in skeletal muscle strength over time.